EFEKTIVITAS MEDIA REALIA MELALUI MODEL INKUIRI TERBIMBING TERHADAP AKTIVITAS BELAJAR DAN PENGUASAAN MATERI STRUKTUR DAN FUNGSI JARINGAN TUMBUHAN - Antun Sutarya; Arwin Achmad; Rini Rita T Marpaung (Universitas Lampung, 2013)
Based on observations and interviews with Biology teacher at SMP N 19 Bandar Lampung obtained information that eighth grade learning outcomes is still low at only 22.22% of students who achieved mastery Minimal Criteria (KKM). This is presumably due to the use of a variety of media as a tool in learning is still rare. Therefore it is necessary to use a medium that media can make students more actively in learning that results belajarpun increased. The purpose of this study was to mengetahuai realia media effectiveness through guided inquiry model of the learning activities and students' mastery of the material. The research design was a pretest posttest non-equivalent, with sempel retrieval technique using a cluster random sampling. Quantitative research data is data is data mastery of the material obtained from the pretest-posttest values were then calculated with the formula N-Gain scores and data analysis using t-test at the 95% level of belief. Qualitative data in the form of student activity data and questionnaire responses of students drawn from the observation. The results of this study indicate an improvement of the control of matter on a class that uses a media realia through guided inquiry models with average pretest ratat the 3.11 increase to the average post-test is 7.78 with N-gain of 68.54. Likewise with student learning activities, from five aspects of student learning activities observed was evident in the first meeting with the average value of learning activities by 60.95% increased to 75.05% in the second peretemuan. As for the students' responses on the effectiveness of media use realia through guided inquiry model of general students were pleased with the learning that has been done. Keywords: media realia, models guided inquiry, the structure and function of plant tissue, learning activities, and mastery of the material.